Narrative of Oppression on the Main Character in Yusuf Idris' Short Story Haditsah Syaraf: Greimas' Perspective/Narasi Penindasan Pada Tokoh Utama dalam Cerpen Haditsah Syaraf Karya Yusuf Idris: Kajian Naratologi A.J Greimas - Angraini, Lia; Al Anshory, Abdul Muntaqim (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
Oppression is a social phenomenon that is often portrayed in literary works as a form of criticism of unequal power relations, especially in short stories that serve as a medium for articulating social reality. The short story Haditsah Syaraf by Yusuf Idris presents a representation of thinking about women through the construction of social norms that control the body and dignity of the main character. This study aims to analyze the actantial and functional narrative structures to reveal these dynamics using qualitative descriptive methods. Data were obtained from the short story Haditsah Syaraf published by Yayasan Hindawi using reading, note-taking, and translation techniques, and analyzed using the Miles and Huberman model. The results show that the actantial structure forms a relational pattern that emphasizes: Fatimah functions as both the subject and the receiver, social norms as the sender, while the community, Gharib, and Faraj become inhibiting actants that reinforce patriarchal domination. George's mother appears as a supporting actant, but is not significant in changing the subject's position. The functional structure shows that the narrative actions are dominated by the inhibitor function, indicating the strong social pressure that encompasses female agency. Thus, this study offers a novelty in the use of Greimas' approach to contemporary Arabic short stories, which have not been widely studied before, and reinforces the understanding that literary texts can be an important medium for reading the reproduction of ideology and social inequality.Penindasan merupakan fenomena sosial yang sering ditampilkan dalam karya sastra sebagai bentuk kritik terhadap hubungan kekuasaan yang timpang, khususnya dalam cerita pendek yang berfungsi sebagai media artikulasi realitas sosial. Cerpen Haditsah Syaraf karya Yusuf Idris menampilkan representasi berfikir terhadap perempuan melalui konstruksi norma sosial yang mengontrol tubuh dan martabat tokoh utama. Penelitian ini bertujuan menganalisis struktur naratif aktansial dan fungsional untuk mengungkap dinamika tersebut dengan menggunakan metode deskriptif kualitatif. Data diperoleh dari cerpen Haditsah Syaraf terbitan Yayasan Hindawi menggunakan tehnik baca,cata dan terjemah, serta dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa struktur aktansial membentuk pola relasional yang mempertegaskan: Fatimah berfungsi sebagai subjek sekaligus penerima, norma sosial sebagai pengirim, sedangkan masyarakat, Gharib, dan Faraj menjadi aktan penghambat yang menguatkan dominasi patriaki. Ibu George muncul sebagai aktan pembantu, namun tidak signifikan dalam mengubah posisi subjek. Struktur fungsional menampilkan bahwa tindakan-tindakan naratif didominasi oleh fungsi penghambat, menunjukkan kuatnya tekanan sosial yang mencakup agensi perempuan. Sehingga, penelitian ini menawarkan kebaruan pada penggunaan pendekatan Greimas terhadap cerpen Arab kontemporer yang belum banyak dikaji sebelumnya dan memperkuat pemahaman bahwa teks sastra dapat menjadi media penting untuk membaca reproduksi ideologi dan ketimpangan sosial.